Efficacy of practising Tai Chi for older people with mild dementia: protocol for a randomised controlled study - Lyu, Jihui (BMJ Open, 2018)
INTRODUCTION: Many studies suggest that Tai Chi exercise is a safe and appropriate mind-body exercise for older people and effectively slows down age-related cognitive decline. A set of bespoke Tai Chi exercise named ‘Cognition Protecting Tai Chi’ (CPT) has been created for older people with cognitive impairments by the research team of geriatricians, neurologists, rehabilitation specialists, experts of sports medicine and experienced practitioners of traditional Chinese medicine. This trial is designed to evaluate its effects on cognitive function, behaviour/moods, risk of falls and activities of daily living of the participants with mild dementia. METHODS AND ANALYSIS: A randomised controlled study will be conducted. Eighty participants with mild dementia will be recruited and randomly allocated to an intervention group and a control group. The intervention group will practice the CPT exercise three times a week for 20 min each time under the guidance of professional therapists. The control group will continue receiving their routine treatments. The duration of this study will be 10 months. All participants will be assessed with a battery of neuropsychological and functional evaluations, which include Mini Mental State Examination, Montreal Cognitive Assessment, the WHO-University of California Los Angeles-Auditory Verbal Learning test (WHO-UCLA-AVLT), Trail Making Test (TMT), Geriatric Depression Scale, Neuropsychological Inventory and Barthel Index, at the baseline, 5 and 10 months during the study period. Fall incident will also be recorded. The primary outcome will be the WHO-UCLA-AVLT delayed recall score. The secondary outcome will be the TMT score. ETHICS AND DISSEMINATION: This study has been approved by the ethical review committee of the Beijing Geriatric Hospital (protocol number: 2015–021). Informed consent will be obtained from all participants or their guardians. The authors intend to submit the findings of the study to peer-reviewed journals or academic conferences to be published. TRIAL REGISTRATION NUMBER: ChiCTR-INR-16009872; Pre-results.